2008
DOI: 10.1002/bdra.20509
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of methylation and changes in gene expression in relation to neural tube defects

Abstract: Inhibition of methylation by Adox affects gene expression in our in vitro chick embryo model. Further research will focus on the gene-specific methylation patterns of PSPH, ULK1, and CXCL12/SDF-1 and the role of the products of these genes in neurulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…Among the local autism mothers, the G allele load was positively correlated with lymphocyte DNA hypomethylation (Table VII and Figure 3). In both animal and human studies, DNA hypomethylation has been negatively correlated with folate status and positively correlated with homocysteine and SAH (van der Linden et al 2008;Chen et al 2001;Niculescu and Zeisel 2002;Jacob et al 1998;Yi et al 2000). Maternal folate insufficiency can stem from genetic aberrations, nutritional deficiencies, and/or environmental exposures that increase folate requirement for DNA synthesis and DNA methylation during fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Among the local autism mothers, the G allele load was positively correlated with lymphocyte DNA hypomethylation (Table VII and Figure 3). In both animal and human studies, DNA hypomethylation has been negatively correlated with folate status and positively correlated with homocysteine and SAH (van der Linden et al 2008;Chen et al 2001;Niculescu and Zeisel 2002;Jacob et al 1998;Yi et al 2000). Maternal folate insufficiency can stem from genetic aberrations, nutritional deficiencies, and/or environmental exposures that increase folate requirement for DNA synthesis and DNA methylation during fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous null embryos for DNMT3B70 , coding for one of the enzymes for DNA methylation is responsible for cranial NTDs [150]. Dysregulation of gene expression has also been observed in chick embryos, treated with methylation inhibitors leading to a widening of the anterior neuropore [151]. On the other hand, NTDs are not observed in null embryos for MTHFR , despite a significant reduction in the methylation ratio and global DNA methylation [152].…”
Section: Putative Mechanisms Of Folates Actionmentioning
confidence: 99%
“…Another study demonstrated that global DNA hypomethylation is associated with NTD‐affected pregnancy (Christman et al, 1993). Several reports have shown that methylation cycle inhibition induces a high frequency of cranial NTDs in cultured mouse and chick embryos (Dunlevy et al, 2006; Van der Linden et al, 2008). Thus, impaired genomic methylation may underlie the complex pathogenesis of NTDs.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that methylation cycle inhibition induces a high frequency of cranial NTDs in cultured mouse and 0736-5748/$36.00 © 2011 Published by Elsevier Ltd on behalf of ISDN. doi:10.1016/j.ijdevneu.2011.06.006 chick embryos (Dunlevy et al, 2006;Van der Linden et al, 2008). Thus, impaired genomic methylation may underlie the complex pathogenesis of NTDs.…”
Section: Introductionmentioning
confidence: 99%